ANTIBACTERIAL ACTIVITY OF ESSENTIAL OILS EXTRACTED FROM MEDICINAL PLANTS AGAINST MULTI-DRUG RESISTANT STAPHYLOCOCCUS AUREUS - S. A. Raja; M. Ashraf; A. A. Anjum; A. Javeed; T. Ijaz; A. Attiq (Journal of Animal and Plant Sciences, 2016)
Multi-drug resistant Staphylococcus aureus has been a major contributor to treatment failure in the last decade in Pakistan and indigenous plants focused for screening of new therapeutic options. Antibacterial properties of indigenous medicinal plants essential oils were determined against MDR S. aureus isolates from patients, associated healthcare workers and healthy community. Antibacterial activity was determined by agar well diffusion assay. Minimum inhibitory concentrations (MIC) of essential oils exhibiting activity against selected MDR S. aureus were calculated using Micro broth dilution method. Five plants essential oils Carum copticum, Anethum sowa, Cuminum cyminum, Myristica fragrans and Zingiber officinale were tested for antibacterial activity against selected MDR S. aureus isolates from three sampling groups. Out of five essential oils, Carum copticum was found to be the most effective followed by Zingiber officinale and Cuminum cyminum. Upon qualitative analysis of five essential oils, Carum copticum, Cuminum cyminum and Zingiber officinale essential oils showed zones of inhibition greater than the standards Vancomycin and Linezolid. Anethum sowa and Myristica fragrans essential oils showed no activity against MDR S. aureus. The mean MIC values obtained for Carum copticum against selected MDR S. aureus isolates from patients, healthcare workers and community were 4.2µl, 1.7 µl and 3.0 µl, respectively. Mean MIC value for Zingiber officinale were 10.8 µl, 3.5 µl and 6.8 µl and for Cuminum cyminum were 43.8 µl, 23.8 µl and 40 µl.  The MIC value of Carum copticum essential oil was least against MDR S. aureus isolates and considered most effective plant oil.
Keywords: Multiple drug resistant Staphylococcus aureus; Post-operative wounds; Healthcare workers; Healthy volunteers from Community; Essential oils; Agar well diffusion assay; Minimum inhibitory concentration